Bilateral End Stage Large Wilms Tumor: US and CT Findings - Aydın, Ayşe Murat; Orhan, Hacı; Koç, Mustafa (Fırat University, 2007)
Wilms tumor is most common urinary system malignancy of childhood and consists 8% of pediatric solid tumors. In 5% cases of Wilms tumor, both kidneys are affected at the same time. Lungs are the primary sites for metastasis. 10% of patients have lung metastasis at the time of diagnosis. The most common presentation of Wilms tumor is the presence of an asymptomatic abdominal mass. Radiologic findings provides valuable information about diagnosis and management of the disease. In this study, we present sonographic, Doppler US and computed tomography findings of an end stage, bilateral, large Wilms tumor with lung metastasis. ©2007, Firat University, Medical Faculty

Wilms tümörü, çocuklarda üriner sistemin en sık görülen tümörüdür. Tüm pediatrik solid tümörlerin %8' ini oluşturur. Wilms tümörlü olguların %5' inde bilateral eşzamanlı tutulum görülür. En sık akciğere metastaz yapar. Tanı konulan hastaların %10' unda akciğer metastazı bulunur. Klinik olarak en sık asemptomatik abdominal kitle şeklinde kendini gösterir. Radyolojik bulgular hastalığın tanısına ve tedavinin planlanmasına önemli katkı sağlamaktadır. Biz bu olgumuzda ileri evre, akciğere multipl metastaz yapmış, bilateral eş zamanlı, dev boyutta, Wilms tümörünün US, Doppler US ve BT bulgularını tanımladık. ©2007, Fırat Üniversitesi, Tıp Fakültesi
İleri Evre Bilateral Dev Wilms Tümörü: US ve BT Bulguları